Polyphenylene sulfide composite material with good epoxy resin adhesion and preparation method thereof
By optimizing the formulation and processing technology of polyphenylene sulfide composite materials, the use of inorganic fillers and end capping agents to improve their bonding performance with epoxy resin, the poor bonding performance of polyphenylene sulfide composite materials and epoxy resins is solved. Problem, stronger bonding strength and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411472216.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-27
AI Technical Summary
The adhesive performance of existing polyphenylene sulfide composite materials and epoxy resins is poor, resulting in the detachment of the capacitor shell from the epoxy resin, affecting the protection of internal components, and the existing modification methods have a negative impact on mechanical properties and flame retardant properties. .
Using composite materials including polyphenylene sulfide, glass fiber, inorganic fillers, elastomer toughening additives, coupling agents and phosphate capping agents, to improve the interfacial polarity and bonding of materials by optimizing formulation and processing technology. performance, reduce the impact on mechanical properties.
The bonding strength between polyphenylene sulfide composite material and epoxy resin is significantly improved, the problems caused by the large-scale use of elastomers are avoided, the mechanical properties are ensured, and the production process is simplified.
Smart Images

Figure CN119192843A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyphenylene sulfide composite materials, in particular to the technical field of polyphenylene sulfide composite materials with good epoxy resin adhesion. Background Art
[0002] Polyphenylene sulfide (PPS) is the most in-demand special engineering plastic at present. It is widely used in environmental protection, automotive industry, electronics, aerospace and other fields due to its high temperature resistance, corrosion resistance, wear resistance, flame retardancy, high rigidity, low water absorption, excellent electrical properties, dimensional stability, melt processability, etc. With the rapid development of new energy vehicles and the electronics industry, the demand for capacitors, the main components in circuits, is increasing. Capacitors are devices that store electric charge and release energy. They play a key role in stabilizing current and voltage, and their outer shell plays an important role in protecting the internal components of the capacitor. Glass fiber reinforced polyphenylene sulfide composite materials have high strength, high flame retardancy, corrosion resistance and insulation, and have become the mainstream material for preparing capacitor shells.
[0003] The capacitor shell and the capacitor need to be encapsulated with epoxy resin. If the bonding performance between the capacitor shell and the epoxy resin is poor, it is easy to cause the capacitor shell and the epoxy resin to separate, and the internal components cannot be effectively protected. Therefore, there is an urgent need for polyphenylene sulfide composite materials with good bonding effect with epoxy resin.
[0004] On the other hand, according to the structure of PPS, there are no highly active or highly polar groups around its chain segments, so it is difficult to modify it by establishing a strong connection with other materials. Most of the existing methods to improve the bonding ability of PPS with epoxy are to blend and modify PPS with a large amount of reactive materials such as epoxy resin, which has a great impact on the mechanical properties of PPS.
[0005] In addition, there are some methods for improving the bonding performance by adding elastomers with strong polarity, such as the Chinese invention application CN 108084711 A, which discloses a PPS special plastic with good bonding with epoxy adhesive, in which a toughening agent anhydride-modified ethylene thermoplastic elastomer is added to the PPS special plastic, which can improve the polarity of PPS and the wettability of PPS to epoxy adhesive, thereby improving the bonding force between PPS and epoxy resin. This type of method usually requires the addition of more polarity-modifying additives, especially the addition of too much elastomer material, which easily causes the problem of large gas emission and difficult extrusion processing. At the same time, it will also significantly affect the mechanical properties, flame retardancy and corrosion resistance of the PPS material itself. Summary of the invention
[0006] In view of the defects of the prior art, the object of the present invention is to provide a new polyphenylene sulfide composite material with good epoxy resin adhesion and a preparation method thereof.
[0007] The technical solution of the present invention is as follows:
[0008] A polyphenylene sulfide composite material with good epoxy resin adhesion comprises the following raw material components in parts by mass: 30-50 parts of polyphenylene sulfide, 30-45 parts of glass fiber, 5-20 parts of inorganic filler, 0-2 parts of elastomer toughening agent, 0.2-0.3 parts of coupling agent, 0.5-1.5 parts of silicone powder and 0.1-0.3 parts of end-capping agent; wherein the end-capping agent is selected from phosphate.
[0009] In the above technical solutions, both the inorganic filler and the capping agent can enhance the interface polarity and bonding ability of the PPS material through their excellent polarity and other properties, thereby improving the bonding performance between PPS and epoxy resin.
[0010] According to some preferred embodiments of the present invention, the inorganic filler is selected from one or more of calcium carbonate, wollastonite, zirconium oxide, and aluminum oxide with a particle size of 1000-3000 mesh.
[0011] According to some preferred embodiments of the present invention, the toughening aid is selected from ethylene-methyl acrylate copolymer and / or ethylene-butyl acrylate copolymer.
[0012] According to some preferred embodiments of the present invention, the coupling agent is selected from silane coupling agent KH-560.
[0013] According to some preferred embodiments of the present invention, the capping agent is selected from aluminum dihydrogen phosphate.
[0014] According to some preferred embodiments of the present invention, the melt index of the polyphenylene sulfide is 500-800 g / 10 min at 316° C. and 5 kg, and / or its number average molecular weight is greater than 30,000.
[0015] According to some preferred embodiments of the present invention, the glass fiber is a flat alkali-free continuous glass fiber with a diameter less than 13 μm.
[0016] According to some preferred embodiments of the present invention, the number average molecular weight of the polyphenylene sulfide is 40,000-50,000.
[0017] The polyphenylene sulfide used in this preferred embodiment has excellent comprehensive properties such as processability and mechanical properties.
[0018] The present invention further provides a method for preparing the polyphenylene sulfide composite material, which comprises: mixing the raw material components and then extruding and granulating them.
[0019] According to some preferred embodiments of the present invention, the preparation method comprises:
[0020] (1) mixing the polyphenylene sulfide, inorganic filler, toughening agent and silicone powder at high speed until they are evenly dispersed, adding the coupling agent and continuing to stir and disperse, and slowly adding the end-capping agent until they are evenly mixed to obtain a mixture;
[0021] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, adding the glass fiber during the melt extrusion process, and then screening and drying the obtained granules to obtain the polyphenylene sulfide composite material with good epoxy resin adhesion; wherein the screw length-to-diameter ratio of the co-rotating twin-screw extruder is greater than 40:1, and the melt extrusion temperature is 220-310°C.
[0022] According to some preferred embodiments of the present invention, the co-rotating twin-screw extruder has ten temperature control zones in sequence, and the temperature controls are respectively: zone 1 220-230°C, zone 2 250-260°C, zone 3 280-290°C, zone 4 300-310°C, zone 5 300-310°C, zone 6 280-290°C, zone 7 280-290°C, zone 8 270-280°C, zone 9 270-280°C, zone 10 230-240°C.
[0023] The present invention has the following beneficial effects:
[0024] (1) The present invention uses a capping agent to modify polyphenylene sulfide, which significantly improves the interfacial polarity of polyphenylene sulfide, so that it has good interfacial adhesion with epoxy resin adhesives; and significantly improves the microscopic bonding between polyphenylene sulfide and glass fiber, thereby increasing the bonding strength between the glass fiber reinforced polyphenylene sulfide composite material and the epoxy resin adhesive;
[0025] (2) The present invention does not use elastomer or uses a small amount of elastomer, thus avoiding the problems caused by the large amount of elastomer used in the prior art and ensuring the strength and other mechanical properties of the composite material;
[0026] (3) The preparation method of the present invention has a short process, simple materials, obvious effects, and is easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the composite material obtained in Example 1.
[0028] Figure 2 This is a scanning electron microscope image of the comparative composite material obtained in Comparative Example 3.
[0029] Figure 3 The surface wetting effects of the composite materials of Example 1 and Comparative Examples 1-3 are compared according to the dyne value test.
[0030] Figure 4 Schematic diagram of the bonding method for testing epoxy bonding performance in the embodiments. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0032] Example 1
[0033] The polyphenylene sulfide composite material with good epoxy resin adhesion of the present invention is prepared by the following steps:
[0034] (1) Add 50 parts by mass of polyphenylene sulfide, 15 parts by mass of calcium carbonate with a particle size of 1000-3000 mesh, 2 parts by mass of toughening agent ethylene-methyl acrylate copolymer and 0.5 parts by mass of silicone powder into a high-speed mixer, and add 0.3 parts by mass of silane coupling agent KH-560 after uniform dispersion, continue to stir and disperse, open the feed port of the high-speed mixer, slowly pour 0.3 parts by mass of end-capping agent aluminum dihydrogen phosphate, stir uniformly, and obtain a mixture;
[0035] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, wherein the co-rotating twin-screw extruder has a screw length-diameter ratio greater than 40:1 and contains ten extrusion temperature control zones, wherein the extrusion temperature of each zone is: 220°C for zone 1, 250°C for zone 2, 280°C for zone 3, 300°C for zone 4, 310°C for zone 5, 290°C for zone 6, 290°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 240°C for zone 10; during the extrusion granulation process, adding alkali-free continuous glass fiber from the feed port of zone 5, and maintaining the addition amount at 40 parts by mass by controlling the number of glass fibers; and obtaining the polyphenylene sulfide composite material with good epoxy resin adhesion through screw shearing dispersion, melt extrusion, water-cooled strand cutting, screening, drying, and packaging.
[0036] The microstructure of the obtained polyphenylene sulfide composite material was characterized as shown in the attached figure. Figure 1 From the SEM images shown, it can be seen that in the obtained material, the interface between the glass fiber and the resin is well bonded.
[0037] Example 2
[0038] The polyphenylene sulfide composite material with good epoxy resin adhesion of the present invention is prepared by the following steps:
[0039] (1) Add 50 parts by mass of polyphenylene sulfide, 15 parts by mass of calcium carbonate with a particle size of 1000-3000 mesh, and 0.5 parts by mass of silicone powder into a high-speed mixer, and after uniform dispersion, add 0.3 parts by mass of silane coupling agent KH-560, continue to stir and disperse, open the feed port of the high-speed mixer, slowly pour 0.3 parts by mass of end-capping agent aluminum dihydrogen phosphate, stir uniformly, and obtain a mixture;
[0040] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, wherein the co-rotating twin-screw extruder has a screw length-diameter ratio greater than 40:1 and contains ten extrusion temperature control zones, wherein the extrusion temperature of each zone is: 220°C for zone 1, 250°C for zone 2, 280°C for zone 3, 300°C for zone 4, 310°C for zone 5, 290°C for zone 6, 290°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 240°C for zone 10; during the extrusion granulation process, adding alkali-free continuous glass fiber from the feed port of zone 5, and maintaining the addition amount at 40 parts by mass by controlling the number of glass fibers; and obtaining the polyphenylene sulfide composite material with good epoxy resin adhesion through screw shearing dispersion, melt extrusion, water-cooled strand cutting, screening, drying, and packaging.
[0041] Comparative Example 1
[0042] A comparative polyphenylene sulfide composite material was prepared by the following steps:
[0043] (1) adding 50 parts by mass of polyphenylene sulfide, 15 parts by mass of calcium carbonate with a particle size of 1000-3000 mesh, 2 parts by mass of toughening agent ethylene-methyl acrylate copolymer and 0.5 parts by mass of silicone powder into a high-speed mixer, and adding 0.3 parts by mass of silane coupling agent KH-560 after uniform dispersion, and continuing to stir and disperse to obtain a mixture;
[0044] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, wherein the co-rotating twin-screw extruder has a screw length-diameter ratio greater than 40:1 and contains ten extrusion temperature control zones, wherein the extrusion temperature of each zone is: 220°C for zone 1, 250°C for zone 2, 280°C for zone 3, 300°C for zone 4, 310°C for zone 5, 290°C for zone 6, 290°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 240°C for zone 10; during the extrusion granulation process, adding alkali-free continuous glass fiber from the feeding port of zone 5, and maintaining the addition amount at 40 parts by mass by controlling the number of glass fibers; and obtaining the comparative polyphenylene sulfide composite material by screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying, and packaging.
[0045] Comparative Example 2
[0046] A comparative polyphenylene sulfide composite material was prepared by the following steps:
[0047] (1) Add 50 parts by weight of polyphenylene sulfide, 2 parts by weight of toughening agent ethylene-methyl acrylate copolymer, and 0.5 parts by weight of silicone powder into a high-speed mixer, and after uniform dispersion, add 0.3 parts by weight of silane coupling agent KH-560, continue to stir and disperse, open the feed port of the high-speed mixer, slowly pour 0.3 parts by weight of end-capping agent aluminum dihydrogen phosphate, and stir uniformly to obtain a mixture;
[0048] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, wherein the co-rotating twin-screw extruder has a screw length-diameter ratio greater than 40:1 and contains ten extrusion temperature control zones, wherein the extrusion temperature of each zone is: 220°C for zone 1, 250°C for zone 2, 280°C for zone 3, 300°C for zone 4, 310°C for zone 5, 290°C for zone 6, 290°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 240°C for zone 10; during the extrusion granulation process, adding alkali-free continuous glass fiber from the feeding port of zone 5, and maintaining the addition amount at 55 parts by mass by controlling the number of glass fibers; and obtaining the comparative polyphenylene sulfide composite material by screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying, and packaging.
[0049] Comparative Example 3
[0050] A comparative polyphenylene sulfide composite material was prepared by the following steps:
[0051] (1) adding 42 parts by mass of polyphenylene sulfide, 10 parts by mass of toughening agent ethylene-methyl acrylate copolymer and 0.5 parts by mass of silicone powder into a high-speed mixer, and adding 0.3 parts by mass of silane coupling agent KH-560 after uniform dispersion, and continuing to stir and disperse to obtain a mixture;
[0052] (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, wherein the co-rotating twin-screw extruder has a screw length-diameter ratio greater than 40:1 and contains ten extrusion temperature control zones, wherein the extrusion temperature of each zone is: 220°C for zone 1, 250°C for zone 2, 280°C for zone 3, 300°C for zone 4, 310°C for zone 5, 290°C for zone 6, 290°C for zone 7, 280°C for zone 8, 280°C for zone 9, and 240°C for zone 10; during the extrusion granulation process, adding alkali-free continuous glass fiber from the feeding port of zone 5, and maintaining the addition amount at 40 parts by mass by controlling the number of glass fibers; and obtaining the comparative polyphenylene sulfide composite material by screw shearing dispersion, melt extrusion, water-cooled strand pelletizing, screening, drying, and packaging.
[0053] The microstructure of the obtained polyphenylene sulfide composite material was characterized as shown in the attached figure. Figure 2 From the SEM images shown, it can be seen that in the obtained material, the glass fiber and resin interface are completely separated.
[0054] Further, a 42 dyne pen was used to determine the surface dyne value of the composite material strips obtained in Example 1 and Comparative Examples 1-3, as shown in the attached figure. Figure 3 As shown, it can be seen that the surface wetting effect of Example 1 is the best, achieving complete wetting; Comparative Example 1 does not use a capping agent, and the surface wetting is significantly worse; Comparative Example 2 does not use calcium carbonate, and the surface wetting effect is weakened to a certain extent; Comparative Example 3 does not use a capping agent but increases the amount of elastomer, and its wettability is also poor.
[0055] For further information, see Attachment Figure 4 The injection molded specimens of the composite materials of Implementation 1-2 and Comparative Examples 1-3 were bonded and pressed with an epoxy adhesive and cured at 120° C. for 12 h, and then the tensile strength was tested. The test results are shown in Table 1.
[0056] Table 1: Epoxy bond strength test results
[0057] Sample No. Adhesion strength (MPa) Example 1 10.8 Example 2 11.3 Comparative Example 1 6.4 Comparative Example 2 7.9 Comparative Example 3 4.8
[0058] It can be seen that the material bonding strength of Examples 1 and 2 is significantly improved compared with Comparative Examples 1-3, and Example 2 has a higher bonding strength.
[0059] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A polyphenylene sulfide composite material having good epoxy resin adhesion, characterized in that: The invention comprises the following raw material components in parts by weight: 30-50 parts of polyphenylene sulfide, 30-45 parts of glass fiber, 5-20 parts of inorganic filler, 0-2 parts of elastomer toughening agent, 0.2-0.3 parts of coupling agent, 0.5-1.5 parts of silicone powder and 0.1-0.3 parts of end-capping agent; wherein the end-capping agent is selected from phosphate.
2. The polyphenylene sulfide composite material according to claim 1, characterized in that: The inorganic filler is selected from one or more of calcium carbonate, wollastonite, zirconium oxide and aluminum oxide with a particle size of 1000-3000 meshes.
3. The polyphenylene sulfide composite material according to claim 1, characterized in that: The toughening aid is selected from ethylene-methyl acrylate copolymer and / or ethylene-butyl acrylate copolymer.
4. The polyphenylene sulfide composite material according to claim 1, characterized in that: The coupling agent is selected from silane coupling agent KH-560.
5. The polyphenylene sulfide composite material according to claim 1, characterized in that: The capping agent is selected from aluminum dihydrogen phosphate.
6. The polyphenylene sulfide composite material according to claim 1, characterized in that: in, The melt index of the polyphenylene sulfide is 500-800 g / 10 min at 316° C. and 5 kg, and / or its number average molecular weight is greater than 30,000; and / or the glass fiber is a flat alkali-free continuous glass fiber with a diameter of less than 13 μm.
7. The polyphenylene sulfide composite material according to claim 6, characterized in that: The number average molecular weight of the polyphenylene sulfide is 40,000-50,000.
8. The method for preparing the polyphenylene sulfide composite material according to any one of claims 1 to 7, characterized in that: It includes: The raw material components are mixed and then extruded into granules.
9. The preparation method according to claim 8, characterized in that: It includes: (1) mixing the polyphenylene sulfide, inorganic filler, toughening agent and silicone powder at high speed until they are evenly dispersed, adding the coupling agent and continuing to stir and disperse, and slowly adding the end-capping agent until they are evenly mixed to obtain a mixture; (2) adding the mixed material into a co-rotating twin-screw extruder for melt extrusion granulation, adding the glass fiber during the melt extrusion process, and then screening and drying the obtained granules to obtain the polyphenylene sulfide composite material with good epoxy resin adhesion; wherein the screw length-to-diameter ratio of the co-rotating twin-screw extruder is greater than 40:1, and the melt extrusion temperature is 220-310°C.
10. The preparation method according to claim 9, characterized in that: The co-rotating twin-screw extruder has ten temperature control zones, and the temperature control zones are: zone 1 220-230°C, zone 2 250-260°C, zone 3 270-280°C, zone 4 290-300°C, zone 5 200-310°C, zone 6 210-320°C, zone 7 220-330°C, zone 8 Zone 1 280-290℃, Zone 4 300-310℃, Zone 5 300-310℃, Zone 6 280-290℃, Zone 7 280-290℃, Zone 8: 270-280℃, Zone 9: 270-280℃, Zone 10: 230-240℃.
Citation Information
Patent Citations
Special PPS (polyphenylene sulfide) plastic having good bonding property with epoxy adhesive and preparation method of PPS plastic
CN108084711A
